Thermal-triggered packing of lipophilic NIR dye IR780 in hepatitis B core at critical ionic strength and cargo-host ratio for improved stability and enhanced cancer phototherapy. (September 2021) - Lu, Fengying; Li, Zhengjun; Sheng, Yanan; Ma, Yanyan; Yang, Yanli; Ren, Ying; Su, Zhiguo; Yu, Rong; Zhang, Songping
Abstract: Virus-like particles (VLPs) holding internal cavity with diameter from tens up to one hundred nanometers are attractive platform for drug delivery. Nevertheless, the packing of drugs in the nanocage mainly relies on complicated disassembly-reassembly process. In this study, hepatitis B core protein (HBc) VLPs which can withstand temperature up to 90 °C was employed as carrier to load a lipophilic near infrared dye IR780. It was found that an attaching-dis-atching-diffusing process was involved for the entering of IR780 in the cavity of HBc. The first two steps were associated with the electrostatic interactions between oppositely charged HBc and IR780, which was critically manipulated by ionic strength and HBc/IR780 mass ratio at which they were mixed; while the diffusion of IR780 across the shell of HBc showed a temperature-dependent manner that can be triggered by thermal induced pore-opening of the HBc capsid. At optimized condition, about 1055 IR780 molecules were encapsulated in each HBc by simply mixing them for 10 min at 60 °C. Compared with free IR780, the HBc-IR780 particles showed significantly improved aqueous and photostability, as well as enhanced photothermal and photodynamic performance for cancer therapy. This study provides a novel drug loading strategy and nanomemedicine for cancer phototherapies.